Strategies for Naming Japanese Fantasy Light Novels in Thai Language - Inthisaeng, Saranya; Keawsalee, Atchariya; Saard, Sudarat; Chummuel, Chakhariya (Fa Nuea Journal, 2025)
The purpose of this research is to examine the strategies for naming Japanese fantasy light novels in Thai language. The study analyzed the titles from a total of 25 light novels published by Phoenix Next, Zenshu, A-plus, and Bongkoch Comics, utilizing the title-naming strategies proposed by Thakerng Phanthakerngamorn (1998). Each title may employ a combination of multiple naming strategies. The study identified 10 different naming strategies. The most frequently used strategy was naming based on the main theme or key concept of the story, either as a single strategy or in combination with others. Additionally, an interesting finding was that Thai naming strategies often incorporated other fantasy-related elements, such as a character’s main characteristic, names of places, and important items featured in the story. The use of titles that clearly reflect both the main theme and these fantasy-related elements helps to enhance memorability and also effectively convey the content of the story to readers.